Towards cavity quantum electrodynamics and coherent control with single InGaN/GaN quantum dots - Reid, BPL (2013)
Experimental investigations of the optical properties of InGaN/GaN quantum dots are presented. A pulsed laser is used to perform time-integrated and time-resolved microphotoluminescence, photoluminescence excitation, and polarisation-resolved spectroscopy of single InGaN quantum dots under a non-linear excitation regime. The first micro-photoluminescence results from InGaN/GaN quantum dots grown on a non-polar crystal plane (11-20) are presented. Time-resolved studies reveal an order of magnitude increase in the oscillator strength of the exciton transition when compared to InGaN quantum dots grown on the polar (0001) plane, suggesting a significantly reduced internal electric field in non-polar InGaN quantum dots. Polarisation resolved spectroscopy of non-polar InGaN quantum dots reveals 100% linearly polarised emission for many quantum dots. For quantum dot emissions with a polarisation degree less than unity, a fine structure splitting between two orthogonal polarisation axes can be resolved in an optical setup with a simple top-down excitation geometry. A statistical investigation into the origins of spectral diffusion in polar InGaN quantum dots is presented, and spectral diffusion is attributed to charge carriers trapped at threading dislocations, and itinerant and trapped carriers in the underlying quantum well layer which forms during the growth procedure. Incorporating quantum dots into the intrinsic region of a p-i-n diode structure and applying a reverse bias is suggested as a method to reduce spectral diffusion. Coherent control of the excited state exciton in a non-polar InGaN quantum dot is experimentally demonstrated by observation of Rabi rotation between the excited state exciton and the crystal ground state. The exciton ground state photoluminescence is used as an indirect measurement of the excited state population.